Perceived sweetness of sugar and low-calorie sweetener among adults: the fatter, the sweeter - Wan Mahmood, Wan Fathin Fariza; Mamat, Nik Mazlan; Jalaluddin, Nur Khairunissa; Abu Bakar, Nurul Husna; Mohd. Abu Bakar, Wan Azdie (2012)
Background: Excessive sugar intake has been identified as one of the contributors to the increased prevalence of metabolic syndromes. Thus, the awareness to control sugar intake must be emphasized. Objectives: This research aimed to measure the relationship between Body Mass Index (BMI) and fat percentage with sweetness perception among adults; and to compare the sweetness perception of sugar and low-calorie sweeteners (LCS) with different BMI and fatness status. Methodology: A total of 160 adults (18-59 y) tasted 18 liquid (tea) and solid food (butter cookie) samples prepared using 3 sweeteners (sugar, stevia and aspartame); each concocted into 3 levels of sweetness; Level 2 represents the relatively usual sweetness. Respondents rated their perceived sweetness for each sample on a 100mm visual analogue scale (VAS). The BMI and bodyfat percentage data were collected. Results: There are significant weak positive correlations between BMI and sweetness perception for tea samples at the highest concentration of sugar, stevia and aspartame (r=0.159; 0.223; 0.238 respectively, p<0.05) and cookie sample with highest concentration of aspartame (r=0.167, p=0.035). More prominent significant correlation was observed between fatness and sweetness perception for most concentration of sweeteners in liquid and solid samples. Obese respondents showed significant higher score of perceived sweetness than lean counterparts for all liquid samples with highest concentration of sweeteners (Teasugar 81.5 vs 75.0, p=0.041; Teastevia 71.2 vs 59.7, p=0.003; Teaaspartame 70.0 vs 59.0, p=0.001), but not significant for solid food samples. Respondents with higher bodyfat percentage showed significantly higher perceived sweetness for nearly all liquid samples, except sugar and stevia at lowest concentration. Conclusion: Adults with higher BMI and bodyfat tend to perceive sweetness more than the lean person. This is true even at a relatively lower concentration of LCS. This suggests that replacing sugar with LCS is acceptable and beneficial in reducing calorie intake.